Tecnología y aprendizaje organizacional factores influyentes sobre la satisfacción profesional en residentes de pregrado - López-Lemus, Jorge Armando; De la Garza Carranza, María Teresa (Universidad de Costa Rica, 2018)
The research article analyzes the use of technology, organizational learning and its influence on the personal satisfaction of undergraduate residents in industrial companies. The design and methodology includes a sample of 220 undergraduate residents from the Guanajuato state, Mexico. The methodological design of the research was quantitative, explanatory, observational and cross-sectional and the instruments used allow the measure of the selected variables. To test the established hypotheses, a structural equation model (SEM) was developed in the research. Through the SEM model, it is demonstrated that the use of technology is a factor that positively and significantly influences the organizational learning of undergraduate residents. Likewise, the use of technology positively and significantly influences the personal satisfaction of university residents. On the other hand, organizational learning positively and significantly influences the personal satisfaction of undergraduate interns in industrial companies in the Guanajuato state, Mexico. This research promotes a discussion on the use of technologies, organizational learning and professional satisfaction of the undergraduate residents of the state of Guanajuato. The objective of the present research study was to know the influence exerted by the technology of the undergraduate residents and the organizational learning on their personal satisfaction in the incorporation in the industrial sector